RO pagpatokasog it mga pumueuyo sa Katunggan documentation and assessment of Katunggan it Ibajay. - Redison, Steffany R. (2016.)
This study documents and assesses the processes involved in the establishment of Katunggan it Ibajay Eco-Park (KII) located in Barangay Bugtongbato and Barangay Naisud in Ibajay, Aklan. KII houses 27 out of the 36 species of mangroves species endemic in the Philippines. This qualitative study used narrative and descriptive techniques. Four (4) sets of Focus Group Discussions (FGDs) and twelve (12) sets of Key Informant Interviews were conducted with research participants coming from two barangays and the stakeholders of KII. Secondary data review and informal interviews were also conducted. The results of this study show that the establishment of KII is due to economic and resource protection factors. It is being hoped that with KII, issues including poverty and resource degradation can be gradually addressed. KII is also expected to help reduce resource dependence and disaster risk while promoting environmental integrity and local economic development. The identified challenges in the process are disunity among stakeholders, continuing resource extraction and disjoint in plans and policies especially at the level of people?s organizations and the barangay LGUs. The findings of this support the need for the inclusion and integration of CRM efforts in local development planning, and the revitalization of Pos vis-à-vis the barangay councils of Bugtongbato and Naisud.
Research Study (Undergraduate, Bachelor of Arts in Community development-Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Eco Park -- Ibajay, Aklan